2005
DOI: 10.1002/mrm.20374
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced MRI in normal and abnormal prostate tissues as defined by biopsy, MRI, and 3D MRSI

Abstract: This study characterized dynamic contrast-enhanced (DCE) MRI of prostate tissues: cancerous peripheral zone (PZ), normal PZ, stromal benign prostatic hyperplasia (BPH), and glandular BPH. MRI, MRSI, and DCE MRI were performed on 25 patients. Tissues were identified with MRI, MRSI, and (when available) biopsy results. Motion between MRI and DCE MRI, and within DCE MRI was assessed and manually corrected. To assess tissue and patient effects, native T 1 's were measured in 12 of 25 patients, and DCE MRI results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 21 publications
6
85
0
Order By: Relevance
“…In the last few years we have seen a technological leap in non-invasive imaging technologies such as magnetic resonance (MR) imaging (MRI). Thus, there is an exciting opportunity to apply the new imaging techniques to the pancreatic beta cell [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years we have seen a technological leap in non-invasive imaging technologies such as magnetic resonance (MR) imaging (MRI). Thus, there is an exciting opportunity to apply the new imaging techniques to the pancreatic beta cell [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms can have a significant effect on quality of life and can eventually lead to acute urinary retention, which requires surgical intervention (9). Measuring baseline microvascular parameters of BPH is valuable because distinguishing BPH, cancer, and normal tissue can be difficult, often requiring the use of several different techniques in consensus (10). By comparing these measurements with values estimated in cancer and normal tissue (6,11), suitable parameters for differential diagnosis of BPH may be identified.…”
mentioning
confidence: 99%
“…On the other hand, Preziosi et al 3 showed significant differences for prostate cancer in mean tumor maximal enhancement, mean tumor rise time and greatest washout slope versus normal prostate. The nonspecificity was emphasized by Nowlrowski et al, 4 who reported that maximal intensity enhancement and fastest peak occurs with stromal hyperplasia exceeding that of even cancer. Padhani et al 5 showed no peak enhancement differences, permeability or leakage modeling parameters between the medial zone and cancer.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4][5][6] The angiogenesis of prostatic cancer stimulates increased vessel growth and density (maximum vessel density) as compared to normal tissue. 1,2 Accordingly, DCE MRI of the tumor tissue demonstrates increased signal intensity reflecting the increased number of tumor blood vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation